(x+0.2)(x+3.9)=0

Simple and best practice solution for (x+0.2)(x+3.9)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+0.2)(x+3.9)=0 equation:


Simplifying
(x + 0.2)(x + 3.9) = 0

Reorder the terms:
(0.2 + x)(x + 3.9) = 0

Reorder the terms:
(0.2 + x)(3.9 + x) = 0

Multiply (0.2 + x) * (3.9 + x)
(0.2(3.9 + x) + x(3.9 + x)) = 0
((3.9 * 0.2 + x * 0.2) + x(3.9 + x)) = 0
((0.78 + 0.2x) + x(3.9 + x)) = 0
(0.78 + 0.2x + (3.9 * x + x * x)) = 0
(0.78 + 0.2x + (3.9x + x2)) = 0

Combine like terms: 0.2x + 3.9x = 4.1x
(0.78 + 4.1x + x2) = 0

Solving
0.78 + 4.1x + x2 = 0

Solving for variable 'x'.

Begin completing the square.

Move the constant term to the right:

Add '-0.78' to each side of the equation.
0.78 + 4.1x + -0.78 + x2 = 0 + -0.78

Reorder the terms:
0.78 + -0.78 + 4.1x + x2 = 0 + -0.78

Combine like terms: 0.78 + -0.78 = 0.00
0.00 + 4.1x + x2 = 0 + -0.78
4.1x + x2 = 0 + -0.78

Combine like terms: 0 + -0.78 = -0.78
4.1x + x2 = -0.78

The x term is 4.1x.  Take half its coefficient (2.05).
Square it (4.2025) and add it to both sides.

Add '4.2025' to each side of the equation.
4.1x + 4.2025 + x2 = -0.78 + 4.2025

Reorder the terms:
4.2025 + 4.1x + x2 = -0.78 + 4.2025

Combine like terms: -0.78 + 4.2025 = 3.4225
4.2025 + 4.1x + x2 = 3.4225

Factor a perfect square on the left side:
(x + 2.05)(x + 2.05) = 3.4225

Calculate the square root of the right side: 1.85

Break this problem into two subproblems by setting 
(x + 2.05) equal to 1.85 and -1.85.

Subproblem 1

x + 2.05 = 1.85 Simplifying x + 2.05 = 1.85 Reorder the terms: 2.05 + x = 1.85 Solving 2.05 + x = 1.85 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.05' to each side of the equation. 2.05 + -2.05 + x = 1.85 + -2.05 Combine like terms: 2.05 + -2.05 = 0.00 0.00 + x = 1.85 + -2.05 x = 1.85 + -2.05 Combine like terms: 1.85 + -2.05 = -0.2 x = -0.2 Simplifying x = -0.2

Subproblem 2

x + 2.05 = -1.85 Simplifying x + 2.05 = -1.85 Reorder the terms: 2.05 + x = -1.85 Solving 2.05 + x = -1.85 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.05' to each side of the equation. 2.05 + -2.05 + x = -1.85 + -2.05 Combine like terms: 2.05 + -2.05 = 0.00 0.00 + x = -1.85 + -2.05 x = -1.85 + -2.05 Combine like terms: -1.85 + -2.05 = -3.9 x = -3.9 Simplifying x = -3.9

Solution

The solution to the problem is based on the solutions from the subproblems. x = {-0.2, -3.9}

See similar equations:

| 28d+1=28 | | x^2+4x+28=0 | | x+x(.04)=2.75 | | 3(7-2h)=9 | | x^2=y-1 | | -s+3=52+21 | | x^2+34x+2= | | -x^2+565x-8250=0 | | (x-y)(x^2-10xy+y^2)=0 | | b-[x+4a+(x-7)]= | | 9+4+4v-2v+6=11 | | 15.6=2x-1.2 | | 80-2(p+1)=-20+48p | | .006x^3=6572 | | 3-2(2)-5=5(2)-22+3(2) | | 144=4q+4q | | 4x-3=3(-1+x) | | x+6forx=13 | | 120=p+7p | | 2x-3=-4+x | | 3x+(4x-1)=90 | | 0.1t=.4+.3t | | 8m+m=90 | | X+2x-1=2(-1+x) | | (4x^2-9x-9)= | | -x^2+515x-7500=0 | | 10x-45=3(b-15) | | h(t)=196-16t^2 | | x^2+515x-7500=0 | | -3n+3(5n-4)=8n-2(-8n+6) | | 6n+2n=96 | | 5x-(8x+4)=8x+-15 |

Equations solver categories